Current Symptomatic and Disease-Modifying Treatments in Multiple System Atrophy - Meszaros, Lisa; Hoffmann, Alana; Wihan, Jeanette; Winkler, Jürgen (International Journal of Molecular Sciences, 2020)
Multiple system atrophy (MSA) is a rare, severe, and rapidly progressive neurodegenerative disorder categorized as an atypical parkinsonian syndrome. With a mean life expectancy of 6-9 years after diagnosis, MSA is clinically characterized by parkinsonism, cerebellar ataxia, autonomic failure, and poor l-Dopa responsiveness. Aside from limited symptomatic treatment, there is currently no disease-modifying therapy available. Consequently, distinct pharmacological targets have been explored and investigated in clinical studies based on MSA-related symptoms and pathomechanisms. Parkinsonism, cerebellar ataxia, and autonomic failure are the most important symptoms targeted by symptomatic treatments in current clinical trials. The most prominent pathological hallmark is oligodendroglial cytoplasmic inclusions containing alpha-synuclein, thus classifying MSA as synucleinopathy. Additionally, myelin and neuronal loss accompanied by micro- and astrogliosis are further distinctive features of MSA-related neuropathology present in numerous brain regions. Besides summarizing current symptomatic treatment strategies in MSA, this review critically reflects upon potential cellular targets and disease-modifying approaches for MSA such as (I) targeting α-syn pathology, (II) intervening neuroinflammation, and (III) neuronal loss. Although these single compound trials are aiming to interfere with distinct pathogenetic steps in MSA, a combined approach may be necessary to slow down the rapid progression of the oligodendroglial associated synucleinopathy.
CRIS-Team Scopus Importer:2020-06-09
Keywords: disease-modifying therapy; drug development; multiple system atrophy; parkinsonian disorders